(untitled) (Swiss Medical Weekly, 2012)
Vitamin D deficiency is associated with risk in several diseases. Vitamin D status has high heritability, yet the genetic epidemiology of vitamin D or its metabolites has not been well studied. Our objective was to identify the relationship among three vitamin D-related genes (GC, CYP2R1 and DHCR7/NADSYN1) and the levels of 25(OH)D in northeastern Han Chinese children. A total of 506 northeastern Han Chinese children were enrolled in this study. Linear regression was used to examine the impact of 12 SNPs on 25(OH)D concentrations after adjustment for age, gender, BMI and regular usage of vitamin D, and Bonferroni’s method was adopted for multiple corrections. The two SNPs in GC (rs222020, rs2298849), four SNPs in CYP2R1 (rs10741657, rs10766197, rs12794714 and rs1562902) and two SNPs in DHCR7/NADSYN1 (rs3829251, rs12785878) were significantly associated with plasma 25(OH)D concentrations under both additive and recessive models (P <0.05). The genotypes of the CYP2R1rs2060793 polymorphism showed positive association with serum 25(OH)D status under all of the three genetic models even after correction for multiple comparison. This population-based study was the first to confirm the strong effects of the GC, CYP2R1 and DHCR7/NADSYN1 loci on circulating 25(OH)D concentrations in northeastern Han Chinese children.